Disease-specific mortality burdens in a rural Gambian population using verbal autopsy, 1998-2007 - Momodou Jasseh; Stephen R. C. Howie; Pierre Gomez; Susana Scott; Anna Roca; Mamady Cham; Brian Greenwood; Tumani Corrah; Umberto D'Alessandro (Taylor & Francis Group, 2014)
Objective: To estimate and evaluate the cause-of-death structure and disease-specific mortality rates in a rural area of The Gambia as determined using the InterVA-4 model. Design: Deaths and person-years of observation were determined by age group for the population of the Farafenni Health and Demographic Surveillance area from January 1998 to December 2007. Causes of death were determined by verbal autopsy (VA) using the InterVA-4 model and ICD-10 disease classification. Assigned causes of death were classified into six broad groups: infectious and parasitic diseases; cancers; other non-communicable diseases; neonatal; maternal; and external causes. Poisson regression was used to estimate age and disease-specific mortality rates, and likelihood ratio tests were used to determine statistical significance. Results: A total of 3,203 deaths were recorded and VA administered for 2,275 (71%). All-age mortality declined from 15 per 1,000 person-years in 1998-2001 to 8 per 1,000 person-years in 2005-2007. Children aged 1-4 years registered the most marked (74%) decline from 27 to 7 per 1,000 person-years. Communicable diseases accounted for half (49.9%) of the deaths in all age groups, dominated by acute respiratory infections (ARI) (13.7%), malaria (12.9%) and pulmonary tuberculosis (10.2%). The leading causes of death among infants were ARI (5.59 per 1,000 person-years [95% CI: 4.38-7.15]) and malaria (4.11 per 1,000 person-years [95% CI: 3.09-5.47]). Mortality rates in children aged 1-4 years were 3.06 per 1,000 person-years (95% CI: 2.58-3.63) for malaria, and 1.05 per 1,000 person-years (95% CI: 0.79-1.41) for ARI. The HIV-related mortality rate in this age group was 1.17 per 1,000 person-years (95% CI: 0.89-1.54). Pulmonary tuberculosis and communicable diseases other than malaria, HIV/AIDS and ARI were the main killers of adults aged 15 years and over. Stroke-related mortality increased to become the leading cause of death among the elderly aged 60 years or more in 2005-2007. Conclusions: Mortality in the Farafenni HDSS area was dominated by communicable diseases. Malaria and ARI were the leading causes of death in the general population. In addition to these, diarrhoeal disease was a particularly important cause of death among children under 5 years of age, as was pulmonary tuberculosis among adults aged 15 years and above.